Active faulting of the Nanhe Fault and relation to the Anninghe Fault zone in the late Quaternary, eastern Tibetan Plateau - Ma, Chao; Liu, Yufa; An, Like; Yang, Xing; Liu, Shao; Zhang, Wei (Frontiers in Earth Science, 2023)
Faults along active block boundaries are the primary structures responsible for great earthquakes in mainland China, to find out the geometric distribution, rupture behavior and paleoseismic history of boundary faults are the basis for understanding regional seismic risk and geodynamic model. The Nanhe fault, located to the east boundary of Sichuan-Yunnan block near the Mianning county, pays less attention due to insufficient historical records of large earthquakes. Focusing on this, we conducted satellite imagery interpretation, field investigations, and trench excavations, suggesting that the Nanhe fault starts from north of the Mianning county near the Anninghe fault in the northeastern section, extending for about 70km southwesward, and terminates southwest of Ermaga village. It has been active faulting with the left-lateral strike-slip rate of 2.4-2.56mm/yr since the late Late Pleistocene, meanwhile, the left-lateral strike and vertical slip rate being 2.5-2.6mm/yr and about 0.6mm/yr in the late Holocene respectively. By trench excavations across the Nanhe fault, three paleoseismic events (5373-4525 BC, AD 1193-1576, AD 1496-1843) were identified, comparative analysis of paleoearthquake events between the Nanhe fault and the Anninghe fault, indicative of that the Anninghe fault and the Nanhe fault may produce cascade rupture or trigger earthquakes, and such related events may occur in 1496-1627. In addition, by comparing the kinematic relationship in eastern boundary faults of Sichuan-Yunnan block, we propose that the Nanhe fault takes part in strain partitioning along the boundary, which reasonably explains the loss of sliding rate between the Anninghe fault and the Zemuhe fault, which is also supports the GPS inversion results and the discontinuous deformation model of the eastern edge of the Tibetan Plateau.